Inactivating calcium-sensing receptor mutations in patients with primary hyperparathyroidism - Frank-Raue, Karin; Leidig-Bruckner, Gudrun; Haag, Christine; Schulze, Egbert; Zink-Lorenz, Angela Maria; Schmitz-Winnenthal, Friedrich Hubertus; Raue, Friedhelm (Clinical endocrinology, 2011)
Objective Primary hyperparathyroidism (HPT) is characterised by autonomous secretion of PTH from enlarged parathyroid glands leading, in most patients, to asymptomatic hypercalcaemia. Familial hypocalciuric hypercalcaemia (FHH) is an autosomal dominant disorder caused by inactivating mutations in the calcium-sensing receptor (CaSR) gene; it is characterised by lifelong and usually asymptomatic hypercalcaemia. Establishing the correct diagnosis is important because surgery can be curative in HPT, but ineffective in FHH. There is overlap in the diagnostic criteria for the two disorders and some patients carrying inactivating mutations in the CaSR gene, which is suggestive of FHH, also have HPT with hyperplastic parathyroid glands or adenomas. Design and patients CaSR gene mutations were analysed and clinical and biochemical parameters evaluated in 139 consecutive outpatients presenting with hypercalcaemia and suspected of having HPT. Results Six different mutations of the CaSR gene were found in eight patients. In four patients, classical FHH was suspected based on clinical and biochemical results and was confirmed by the CaSR mutations. In the other four patients, HPT was diagnosed based on the biochemical profile or symptoms; in these four patients, the parathyroids were operated on and single adenomas were histologically confirmed. In all four patients, serum calcium decreased postoperatively; and in three patients, serum calcium normalised postoperatively. The CaSR mutations in these patients were R25X, E250K and Q926R. Conclusion The coexistence of HPT and FHH in four of 139 patients suggests a pathogenetic role of CaSR mutations in HPT. Despite also having a CaSR mutation, these patients benefited from parathyroid surgery.